The Saga of Ambrosius and Rosamunda: A Parallel Translation of the Oldest Icelandic Version in AM 576 b 4to - McDonald, Sheryl (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2025)
This article presents the first English translation of any version of Ambrósíus saga og Rósamunda, an Icelandic chapbook translation that survives in 20 manuscripts, the oldest being an abridged version of the narrative in AM 576 b 4to, dated to c. 1700. This abridged and oldest witness is translated here, accompanied by an edition of the early modern Icelandic text. The romance recounts the adventures of the young merchant Ambrosius, his bride Rosamunda, and his friend Marsilius, and includes motifs that circulated widely in pre-modern European literature such as the pound of flesh motif and Whittington’s cat. The text was very likely translated into Icelandic from aDanish chapbook in the latter half of the seventeenth century.